Relationship between money growth and inflation : Empirical evidence from Nigeria - Hassan, Jakada Aminu (2015)
This study examines the relationship between money growth and inflation in Nigeria using cointegration and causality analysis. The study used annual time series data from 1970 to 2012, Johansen cointegration approach, Vector Error Correction Model (VECM) and Granger causality test are used to identify long run relationship, the short run dynamic and causal relationship among the variables respectively. The empirical results confirm that in the long run money supply growth has significant and positive relationship with inflation while lagged value of money supply growth has negative and insignificant relationship with inflation in the short run. Moreover, the causality test result reveals that money supply growth has unidirectional causal relationship with inflation, the causal relationship runs from money supply growth to inflation. However, interest rates and import have positive and significant relationship with inflation but exchange rates and GDP have negative and significant relationship with inflation in the long run. In the short run lagged GDP variable has significant and positive relationship with inflation, lagged import variable and lagged interest rate variable have significant and negative relationship with inflation, while lagged of exchange rate variable has insignificant and negative relationship with inflation in the short run. Moreover, the causality test result reveals that exchange rate, interest rates and GDP variable have unidirectional, bidirectional and no causal relationship with inflation, respectively. The study concludes that for maintaining price stability and minimum rate of inflation, Nigeria needs to reduce money supply growth, improve GDP, reduce interest rate and impose strong import restrictions measures as well as exchange rate depreciation along with import substitution strategy.